2022
DOI: 10.1055/s-0042-1749459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preanesthetic Fluid Loading on Postinduction Hypotension and Advanced Cardiac Parameters in Patients with Chronic Compressive Cervical Myelopathy: A Randomized Controlled Trial

Abstract: Purpose Hypotension during the early intraoperative phase is common and can lead to adverse perioperative outcomes. Fluid preloading is one of the methods to limit its occurrence. Patients with chronic compressive cervical myelopathy may have autonomic dysfunction, which can aggravate hemodynamic alterations during anesthesia. This study compared the occurrence of postinduction hypotension and changes in cardiac dynamic indices in patients with and without crystalloid preloading undergoing decompressive cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Firstly, we assessed CAD by using a relatively novel device, ANSiscope™. Though this instrument has been used across diverse groups of patients,[ 5 6 7 8 9 ] its validation with conventional ANS assessment tools is needed before routine use in the perioperative setting. Secondly, we performed the ANS function assessments in the operating room’s preoperative holding area just before the induction of anaesthesia for surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we assessed CAD by using a relatively novel device, ANSiscope™. Though this instrument has been used across diverse groups of patients,[ 5 6 7 8 9 ] its validation with conventional ANS assessment tools is needed before routine use in the perioperative setting. Secondly, we performed the ANS function assessments in the operating room’s preoperative holding area just before the induction of anaesthesia for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time heart rate variability (HRV) assessment using the ANSiscope™ equipment informs about the sympathovagal balance. Previous studies have demonstrated this device’s validity[ 4 ] and utility in the perioperative period during electroconvulsive therapies,[ 5 ] cervical spine,[ 6 ] intracranial[ 7 ] cardiac,[ 8 ] and obstetric surgeries. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…12 Also, a preanesthetic crystalloid fluid bolus may improve postinduction hypotension. 13 An arterial line should be considered when blood pressure lability is expected due to blood loss, hypovolemia, or specific risk factors. Additional monitoring devices can be considered depending on the patient’s comorbidities (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent and treat these hemodynamic deteriorations, studies related to prone positioners [ 4 , 10 , 11 ] or the adjustment of fluid preloading to compensate for the decrease in relative circulatory volume [ 8 , 12 , 13 ] have been conducted. In studies related to fluid administration, parameters such as stroke volume variation (SVV) and pulse pressure variation (PPV) are mainly used to determine fluid responsiveness [ 14–16 ].…”
Section: Introductionmentioning
confidence: 99%